1995
DOI: 10.1128/iai.63.12.4944-4945.1995
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant function of melanin in black fungi

Abstract: Dihydroxynaphthalene melanin in Wangiella dermatitidis and Alternaria alternata was titrated in vivo with the oxidants permanganate, hypochlorite, and H 2 O 2. Melanized strains neutralized more oxidant and withstood higher concentrations of permanganate and hypochlorite than albino strains did. H 2 O 2 killing required 1,000-fold higher concentrations, and melanin did not protect W. dermatitidis against H 2 O 2 .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0
3

Year Published

2001
2001
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(49 citation statements)
references
References 20 publications
2
44
0
3
Order By: Relevance
“…Melanized cryptococcal cells were also more resistant to oxygen-and nitrogen-derived radicals than non-melanized cells (Wang and Casadevall, 1994c;Wang et al, 1995). DHN melanin in E. dermatitidis and A. alternata protects against permanganate and hypochlorite (Jacobson et al, 1995). As with C. neoformans (Jacobson and Tinnell, 1993), melanin did not limit the effects of H 2 O 2 , a weak fungicide, on E. dermatitidis cells (Jacobson et al, 1995).…”
Section: Protection Against Oxidantsmentioning
confidence: 92%
See 1 more Smart Citation
“…Melanized cryptococcal cells were also more resistant to oxygen-and nitrogen-derived radicals than non-melanized cells (Wang and Casadevall, 1994c;Wang et al, 1995). DHN melanin in E. dermatitidis and A. alternata protects against permanganate and hypochlorite (Jacobson et al, 1995). As with C. neoformans (Jacobson and Tinnell, 1993), melanin did not limit the effects of H 2 O 2 , a weak fungicide, on E. dermatitidis cells (Jacobson et al, 1995).…”
Section: Protection Against Oxidantsmentioning
confidence: 92%
“…DHN melanin in E. dermatitidis and A. alternata protects against permanganate and hypochlorite (Jacobson et al, 1995). As with C. neoformans (Jacobson and Tinnell, 1993), melanin did not limit the effects of H 2 O 2 , a weak fungicide, on E. dermatitidis cells (Jacobson et al, 1995). Pigmented E. dermatitidis were protected against neutrophil oxidative burst due to polymerized melanin, and not carotenoids or the melanin precursor scytoalone (Schnitzler et al, 1999).…”
Section: Protection Against Oxidantsmentioning
confidence: 93%
“…The precise means by which melanin may contribute to virulence is only partially understood. Several studies have shown that melanin can act as a scavenger of reactive oxygen species that are produced during host defence reactions (Fels et al, 1987;Wang & Casadevall, 1994;Jacobson et al, 1995;Wang et al, 1995;Schnitzler et al, 1999). Melanized cells are less sensitive to killing by reactive oxygen species than are unmelanized mutants or other unmelanized cells.…”
Section: How Pathogens Deal With Host Defence Responsesmentioning
confidence: 99%
“…Melanized Cryptococcus neoformans cells had an approximately 10fold survival rate than the nonmelanized cells when exposed to oxygen and nitrogen free radicals [9]. Melanotic strains of Wangiella dermatitidis and Alternaria alternata can neutralize more oxidant and withstand higher concentrations of permanganate and hypochlorite than albino strains did [25].…”
Section: Antioxidant Activity Of the Hm Melaninmentioning
confidence: 99%